THE CONFLICTS FACED BY SARA FITZGERALD AS SEEN IN JODY PICOULT’S NOVEL MY SISTER’S KEEPER - Indri Larassanti (Universitas Gadjah Mada, 2013)
The main objective of this study is to investigate conflicts that Sara Fitzgerald has to undergo as depicted in a bestselling novel entitled My Sister’s Keeper by Jodi Picoult. This study also aims to see how the conflicts develop.This study uses objective approach to help find the conflicts of Sara Fitzgerald and how her conflicts develop by applying the theory of internal and external conflict also the theory of frustration. The primary data used is the novel itself. The secondary data are the books related to the theory of conflict and articles from the internet.The result of the study shows that there are four main problems that lead Sara Fitzgerald into conflicts. The problems are Sara having a baby, Jesse and Anna feeling neglected, the trial and Anna’s death. The analysis shows that Sara decides to make important decisions for Kate’s life. Sara faces many failures because of her decisions and it leads her to face more problems and creates new obstacles, one of which is Anger; this act of frustration always appears as the manifestation of her actions.